Specificity of lectin‐immobilized fluorescent nanospheres for colorectal tumors in a mouse model which better resembles the clinical disease. (27th June 2014) - Kitamura, Tokio; Sakuma, Shinji; Shimosato, Moe; Higashino, Haruki; Masaoka, Yoshie; Kataoka, Makoto; Yamashita, Shinji; Hiwatari, Ken‐ichiro; Kumagai, Hironori; Morimoto, Naoki; Koike, Seiji; Tobita, Etsuo; et al.
<x xml:space="preserve">Abstract</x> We have been investigating an imaging agent that enables real‐time and accurate diagnosis of early colorectal cancer at the intestinal mucosa by colonoscopy. The imaging agent is peanut agglutinin‐immobilized polystyrene nanospheres with surface poly(N‐vinylacetamide) chains encapsulating coumarin 6. Intracolonically‐administered lectin‐immobilized fluorescent nanospheres detect tumor‐derived changes through molecular recognition of lectin for the terminal sugar of cancer‐specific antigens on the mucosal surface. The focus of the present study was to evaluate imaging abilities of the nanospheres in animal models that reflect clinical environments. We previously developed an orthotopic mouse model with human colorectal tumors growing on the mucosa of the descending colon to better resemble the clinical disease. The entire colon of the mice in the exposed abdomen was monitored in real time with an in vivo imaging apparatus. Fluorescence from the nanospheres was observed along the entire descending colon after intracolonical administration from the anus. When the luminal side of the colon was washed with phosphate‐buffered saline, most of the nanospheres were flushed. However, fluorescence persisted in areas where cancer cells were implanted. Histological evaluation demonstrated that tumors were present in the mucosal epithelia where the nanospheres fluoresced. In contrast, no fluorescence was observed when control mice, without tumors were tested. The lectin‐immobilized fluorescent nanospheres were tumor‐specific and remained bound to tumors even after vigorous washing. The nanospheres nonspecifically bound to normal mucosa were easily removed through mild washing. These results indicate that the nanospheres combined with colonoscopy, will be a clinically‐valuable diagnostic tool for early‐stage primary colon carcinoma. Copyright © 2014 John Wiley & Sons, Ltd.